Apie lietuvių asmenvardžių su kamienais žyg- ir žy-m- raidą - Sinkevičiūtė, Daiva (Baltistica, 2007)
ON THE DEVELOPMENT OF LITHUANIAN NAMES WITH žyg- AND žy-m- STEMS The mixing of the Lithuanian compound name Žyg(i)mantas with a Christian name Zigmantas changed first stem of the compound name from žyg- into zyg- and zig-. It is thought, that the Lithuanian name changed, because its structure is similar to the said Christian name. The variated letters <z> and <ž> at the beginning of the word, and also the varying and <y> were factors, that influenced the mixing of different personal names, which was especially prevalent in central and northern Lithuania. In the western part of Lithuania, the personal name Žyg(i)mantas was further shortened to Žýmantas because of intensive processes of word contractions. The stimulus for this shortening could be other personal names which have the stem žy- (cf. Žý-gaila, Žý-gaudas, Žý-gintas). In the eastern part of Lithuania, the compound personal names with the stem žyg- may have already disappeared, but their remains are most probably shown by the one-stemmed names with žyg-. The nicknames that appeared from compound personal names with the stem žyg- experienced less changes than their basic words, which is why with this one-stem names, it seems, one can support that the personal name Zìgmantas became similar to compound names with a Lithuanian origin. Also the one-stem names with žyg- confirm the development of personal name Žy-mantas from the personal name Žyg(i)mantas.